2011
DOI: 10.1063/1.3530094
|View full text |Cite
|
Sign up to set email alerts
|

Ionic solvation studied by image-charge reaction field method

Abstract: In a preceding paper [J. Chem. Phys. 131, 154103 (2009)], we introduced a new, hybrid explicit/implicit method to treat electrostatic interactions in computer simulations, and tested its performance for liquid water. In this paper, we report further tests of this method, termed the image-charge solvation model (ICSM), in simulations of ions solvated in water. We find that our model can faithfully reproduce known solvation properties of sodium and chloride ions. The charging free energy of a single sodium ion i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 104 publications
(166 reference statements)
0
29
0
Order By: Relevance
“…However, the critical issue to the short-range treatment is to improve its accuracy and remove the possible artifacts arising in it. [10][11][12][13][14] As one of the approaches to address this issue in a shortrange treatment, [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] the zero-multipole (summation) method (ZMM) has been developed. 30 The underlying physical idea is simple, as follows.…”
Section: Introductionmentioning
confidence: 99%
“…However, the critical issue to the short-range treatment is to improve its accuracy and remove the possible artifacts arising in it. [10][11][12][13][14] As one of the approaches to address this issue in a shortrange treatment, [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] the zero-multipole (summation) method (ZMM) has been developed. 30 The underlying physical idea is simple, as follows.…”
Section: Introductionmentioning
confidence: 99%
“…When there are N charges inside the cavity, the use of the FMM will result in a speedup from O ( N log N ) for the Particle Mesh Ewald (PME) to only O ( N ) operations. The ICSM was originally tested systematically using an in-house program written specifically for use with bulk water [1], and later it was further tested through simulations of ions solvated in water using the modified in-house program [9]. For both cases, it has been found that, by using an optimal set of model parameters, the ICSM can faithfully reproduce many known properties of the simulated biological systems.…”
Section: Introductionmentioning
confidence: 99%
“…The polarizability showed an electrostatic saturation behavior, when the solute charge was less than −0.5e. In studies on integral equation theories [17][18][19][20][21][22], the opposite behavior appeared. The polarizability increased as the solute charge became less than −0.5e.…”
Section: Introductionmentioning
confidence: 99%
“…The Born model is frequently adopted as the simplest method in such calculations [3,9,10], where a linear response and continuum medium are assumed. Hence, the response of a solvent's polarization has been examined based on a molecular picture using integral equation theories and molecular simulation methods [13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%